C++ programming principles and practices for scientists and engineers - Bronson, Gary J. (Cengage Learning, 2013)
The book teaches the fundamentals of the C++ language with a gradual refinement of programming skills from procedural to object-oriented. In addition, students are introduced to the fundamentals of software engineering with an emphasis on problem-solving techniques, making the text an ideal choice for both one- and two-semester C++ programming courses.